Analisis Penerimaan Pengguna Sistem Informasi Akademik Menggunakan Integrasi UTAUT (Unified Theory Of Acceptance Use Of Technology) Dan TRA (Theory Of Reasoned Action) - Masroni Dedi Kiswanto; Dedy Syamsuar (UNIVERSITAS INDO GLOBAL MANDIRI)
The Sumatera Selatan University (USS) is an educational institution of Palembang city that is committed to providing the best service to students as an effort to improve the quality of education. One of the academic endeavors is to implement information system. Implementation of the system is expected to help the administrative process to be effective and efficient. This study aims to determine empirically the acceptance of users (Students, Lecturers, Academic Staff) to academic information system of Sumatera Selatan University. This research integrates the theory of UTAUT (Unified of Acceptance and Use of Technology) and TRA (Theory of Reasoned Action) which are used as the basis for explaining the factors that influence technology acceptance. Furthermore, in the data analysis process, the Partial Least Square Structural Equation Model (SEM-PLS) approach was used. The findings of this study indicate that there is a varied relation between exogenous variables and endogenous variables. First, the results of the analysis show that the Attitude (A) and Social Influence (SI) variables have a significant effect on Behavioral Intention (BI). But the variables Performance Expectancy (PE), Effort Expectancy (EE), and were not proven significant. Second, the results of the analysis also show that the variables of Facilitating Condition (FC) and Behavioral Intention (BI) have a significant effect on Use Behavior (UB).Keywords: Technology Acceptance, Academic Information System, UTAUT, TRA, SEM-PLS